Machine Learning in the Climatic Database: Support Vector Machine’s Algorithm to Map Environmental Events in Months of the Year - de Medeiros, Gilvandro; de Santana Junior, Orivaldo; Luiz, John (Anais da Escola Potiguar de Computação e suas Aplicações (EPOCA); 2018: Anais da XI Escola Potiguar de Computação e suas AplicaçõesDO - 10.5753/epoca.2018.13454, 2018)
With the dissemination of Artificial Intelligence (AI), it becomes common the application of machine learning algorithms (ML) to model and solve problems. In this context, we intend to validate the performance of the ML Vector Support Machine (SVM) algorithm using a public climatic database for the city of Natal. The methodology for this consisted of using the data of said base to train and test the algorithm, placing the information referring to the month of the year in function of the other variables of a given climatic event. Once validated, it is considered promising to deepen the study and application of computational intelligence for meteorological and environmental purposes.